High-entropy alloy with constant-elasticity and super-elasticity characteristics and preparation method

By adjusting the chemical composition and phase transition process of high-entropy alloys, constant elasticity and superelastic effects are achieved within a specific temperature range, solving the problem that existing alloys are difficult to have both constant elasticity and superelasticity, and have excellent mechanical properties.

CN119571175APending Publication Date: 2025-03-07XI AN JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411737795.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The modulus of existing superelastic alloys changes dramatically during phase transition, making it difficult to meet the needs of constant elasticity and hyperelasticity at the same time, and it is difficult to have both high strength and excellent mechanical properties.

Method used

By finely adjusting the chemical composition of high-entropy alloys, especially adjusting the ratios of Ti, Zr, Hf, Ni, Co and Cu, the process of martensite phase transformation is controlled, and the martensite size changes from microns to nanometers, thereby achieving a balance of constant elasticity and superelasticity at the macroscopic level.

Benefits of technology

The constant elastic effect of high-entropy alloys in a specific temperature range is achieved, while having superelastic properties and excellent mechanical properties, such as high compressive strength and resilient strain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571175A_ABST
    Figure CN119571175A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy alloy with constant-elasticity and super-elasticity characteristics and a preparation method, the total mass of the high-entropy alloy is 100 wt.%, and the high-entropy alloy comprises the following chemical components (wt.%): 5-10% of Ti, 15-20% of Zr, 35-40% of Hf, 15-20% of Ni, 10-20% of Co and the balance of Cu. The high-entropy alloy has both constant elasticity and superelasticity, and has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and relates to a high entropy alloy with both constant elasticity and superelasticity and a preparation method thereof. Background Art

[0002] Elastic properties are important properties of metal materials. Elastic modulus and elastic strain are both types of elastic properties of materials. On this basis, existing technologies have developed constant elastic alloys with constant elastic modulus within a certain temperature range and superelastic alloys with large recoverable strain. Constant elastic alloys can be used for sensitive components and inductive devices in high-precision instruments, and superelastic alloys can be used in aerospace parts, sensors, and electromechanical equipment automation.

[0003] At present, deep sea and deep space exploration and other fields have put forward higher requirements for metal materials for sensing devices and other components, requiring them to have excellent mechanical properties while having multifunctional characteristics, that is, they have constant elasticity and superelasticity at the same time, and have excellent mechanical properties. However, the existing superelastic alloys are mainly driven by phase change, and their modulus will change dramatically during phase change, which is contrary to the basic requirement that the elastic modulus of constant elastic alloys remains unchanged. It is difficult to obtain a high-strength alloy with both constant elasticity and superelasticity at the same time.

[0004] In recent years, high entropy alloys have been used to design materials with excellent functional properties and mechanical properties. Compared with traditional alloys, high entropy alloys have multiple principal components, and due to the synergistic effect of multiple principal components, a single solid solution phase is formed. At the same time, due to the lattice distortion effect of high entropy alloys, the limitations of traditional alloys such as the difficulty in matching strength and plasticity and the difficulty in combining functional properties and mechanical properties have been broken. They have been widely used in achieving metal strengthening and toughness and functional structural integration. From the simultaneous improvement of metal strength and plasticity to the optimization of the mechanical properties of functional alloys, they play an important role in the fields of aerospace parts manufacturing, mechanical parts, and biomedicine.

[0005] Recently, high entropy alloys have also been used to design constant elastic alloys and super elastic alloys, but the current level of technology is not enough to meet the ideal requirements of both constant elasticity and super elasticity.

[0006] In view of this, the development of new materials that can combine these two properties has become an important direction of current research. Such materials will greatly promote the progress of related technologies, especially in the field of cutting-edge science and technology. Summary of the invention

[0007] In order to overcome the above problems, the present invention proposes a high entropy alloy having both constant elasticity and superelasticity and a preparation method thereof.

[0008] Specifically, the purpose of the present invention is to provide the following aspects:

[0009] In a first aspect, a high entropy alloy is provided, wherein the total mass of the high entropy alloy is 100 wt.%, and the chemical composition includes the following components (wt.%): Ti is 5-10%, Zr is 15-20%, Hf is 35-40%, Ni is 15-20%, Co is 10-20%, and the remaining component is Cu.

[0010] The elastic modulus temperature coefficient of the high entropy alloy in the temperature range of 130-175°C is 1×10 -5 ~1×10 -4 / ℃.

[0011] Wherein, the recoverable strain of the high entropy alloy is 2.5~3.6%.

[0012] Wherein, the compressive strength of the high entropy alloy is 1.8~2GPa.

[0013] Wherein, the compressive fracture strain of the high entropy alloy is 14.3~19.8%.

[0014] Wherein, the elastic modulus of the high entropy alloy is 46.9~90.56Gpa.

[0015] In a second aspect, a method for preparing the high entropy alloy according to the first aspect is provided, the method comprising:

[0016] Step 1, smelting Ti, Zr, Hf, Ni, Co and Cu to obtain an alloy ingot;

[0017] Step 2: post-processing the alloy ingot to obtain the high entropy alloy.

[0018] In step 1, the purity of Ti, Zr, Hf, Ni, Co and Cu is not less than 99.95%.

[0019] In step 2, the post-treatment includes solution treatment and quenching.

[0020] In a third aspect, there is provided an application of the high entropy alloy according to the first aspect or the high entropy alloy prepared according to the method described in the second aspect in deep-sea detection sensing.

[0021] The beneficial effects of the present invention include:

[0022] (1) The high entropy alloy provided by the present invention has both constant elasticity and superelasticity, and has excellent mechanical properties.

[0023] (2) The preparation method of the high entropy alloy provided by the present invention is simple and has a short processing cycle. In particular, the constant elasticity and superelasticity of the high entropy alloy are achieved through element regulation, which provides a new idea for the preparation of constant elastic and superelastic alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.

[0025] In the attached picture:

[0026] Figure 1 The static modulus temperature curve of the high entropy alloy prepared in Example 1 is shown;

[0027] Figure 2 The dynamic modulus temperature curve of the high entropy alloy prepared in Examples 1-3 is shown;

[0028] Figure 3 The room temperature compression cycle stress-strain curve of the high entropy alloy prepared in Example 1 is shown;

[0029] Figure 4 The room temperature compression fracture curves of the high entropy alloys prepared in Examples 1-3 are shown;

[0030] Figure 5 The room temperature compression cycle stress-strain curve of the high entropy alloy prepared in Example 2 is shown;

[0031] Figure 6 The room temperature compression cycle stress-strain curve of the high entropy alloy prepared in Example 3 is shown. DETAILED DESCRIPTION

[0032] The following will refer to the attached Figures 1 to 6 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0033] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.

[0034] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0035] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.

[0036] On the one hand, according to the present invention, a high entropy alloy having both constant elasticity and superelasticity is provided, the total mass of the high entropy alloy is 100 wt.%, and the high entropy alloy includes the following components (wt.%) of the chemical composition: Ti is 5~10%, Zr is 15~20%, Hf is 35~40%, Ni is 15~20%, Co is 10~20%, and the remaining components are Cu; preferably, the high entropy alloy includes the following components (wt.%) of the chemical composition: Ti is 9.5~10%, Zr is 18~18.5%, Hf is 36~36.5%, Ni is 17.5~18%, Co is 10.5~16.5%, and the remaining components are Cu; for example, the high entropy alloy includes the following components (wt.%) of the chemical composition: Ti is 9.7%, Zr is 18.4%, Hf is 36%, Ni is 17.8%, Co is 14.3%, and the remaining components are Cu.

[0037] In the present invention, the martensitic phase transformation process is controlled by finely adjusting the alloy composition, and the transformation of the martensitic size from micrometer scale to nanometer scale is achieved, that is, the martensitic domains of several micrometers to tens of micrometers in the traditional superelastic alloy are suppressed to more than ten nanometers, and the martensitic phase transformation is not reflected in the average structure. This microscopic structural transformation effect has a decisive influence on the macroscopic properties of the material: not only the rate at which the elastic modulus changes with temperature is changed, and the constant elastic effect is achieved, but also due to the characteristics of the nano-scale martensite itself, the high entropy alloy is endowed with superelasticity. The inventors specially set a total of 6 components of Ti, Zr, Hf, Ni, Co and Cu through the selection of a large number of elements, and the high entropy alloy finally obtained has both constant elasticity and superelasticity. The inventors have found that by adjusting the ratio of Co and Cu, especially increasing the Co content, the constant elasticity effect can be effectively improved, so that the high entropy alloy finally exhibits these two characteristics; and considering the influence of lattice defects and point defects on material properties, by adjusting the ratio of Co and Cu and solution treatment and quenching, the balance of constant elasticity and superelasticity is achieved in a specific high entropy alloy system.

[0038] In the present invention, the high entropy alloy has a constant elasticity of 130-175°C, that is, the temperature coefficient of elastic modulus is 1×10 -5 ~1×10 -4 / ℃; the recoverable strain of the high entropy alloy is 2.5~3.6%; the compressive strength of the high entropy alloy is 1.8~2GPa, the compressive fracture strain is 14.3~19.8%, the yield strength is 729~1540MPa, and the elastic modulus is 46.9~90.56Gpa.

[0039] On the other hand, according to the method for preparing the high entropy alloy according to the first aspect provided by the present invention, the method comprises:

[0040] Step 1, smelting Ti, Zr, Hf, Ni, Co and Cu to obtain an alloy ingot;

[0041] Step 2: post-processing the alloy ingot to obtain the high entropy alloy.

[0042] In step 1, the total mass of Ti, Zr, Hf, Ni, Co and Cu is 100wt.%, and the components (wt.%) of Ti, Zr, Hf, Ni, Co and Cu are: Ti is 5-10%, Zr is 15-20%, Hf is 35-40%, Ni is 15-20%, Co is 10-20%, and the balance is Cu; preferably, Ti is 9.5-10%, Zr is 18-18.5%, Hf is 36-36.5%, Ni is 17.5-18%, Co is 10.5-16.5%, and the balance is Cu; for example, Ti is 9.7%, Zr is 18.4%, Hf is 36%, Ni is 17.8%, Co is 14.3%, and the balance is Cu.

[0043] In step 1, in order to obtain a high-purity high-entropy alloy, the purity of Ti, Zr, Hf, Ni, Co and Cu is not less than 99.95%.

[0044] In step 1, arc melting is preferred because the high temperature during arc melting helps to remove impurities in the metal, thereby producing a high-purity high-entropy alloy; and the production efficiency is high.

[0045] Furthermore, before smelting, the vacuum is first evacuated and purged with an inert gas such as argon for 3 to 5 times, and then the vacuum is evacuated to a pressure value less than 2×10 -3 Pa, prevents gas impurities from participating in the reaction, ensures the purity of the smelted metal and prevents metal oxidation.

[0046] In step 1, an inert gas such as argon is used as a protective gas, and the gas pressure during smelting is 0.03~0.06Pa (relative pressure), such as 0.05Pa. Under a certain gas pressure, metal droplets are not easily sputtered, which helps to ensure the safety of the operation; on the one hand, the inert gas prevents the metal from reacting with oxygen, nitrogen, etc. in the air during the smelting process, and on the other hand, the thermal conductivity of argon is small, the arc generated burns stably, the heat is concentrated, the arc column temperature is high, the heat-affected zone is narrow, and the reaction metal is heated more quickly, thereby improving the smelting efficiency.

[0047] In step 1, during smelting, an arc is struck in advance, and then the raw materials Ti, Zr, Hf, Ni, Co and Cu are smelted for 2 to 6 minutes to ensure that all raw materials are completely melted and reach a uniform molten pool state. Preferably, the smelting time is 3 to 4 minutes, for example 3 minutes.

[0048] Furthermore, arc starting preferably uses Ti balls, but graphite rods or tungsten rods can also be used for arc starting. However, graphite rods can also cause side reactions, and tungsten rods have a very high melting point and are more suitable for extremely high temperature smelting processes. Ti has a relatively high melting point (about 1668°C), can exist stably under the high temperature of the arc, and is not easy to evaporate or react quickly; more importantly, the consumption of Ti balls is relatively low, and will not have a significant impact on the composition of the final high entropy alloy.

[0049] Furthermore, the arc striking time is 30 to 90 seconds, for example, 60 seconds. The arc striking time of 30 to 90 seconds is sufficient to stabilize the arc and ensure a smooth smelting process. On the other hand, it can further consume the impurity gas that may exist in the furnace chamber; if the arc striking time is too long, it may lead to excessive consumption of Ti balls and affect the smelting efficiency.

[0050] In step 1, the smelting operation is performed 3 to 8 times, preferably 5 to 6 times, for example 6 times (arc initiation and smelting the raw materials for 2 to 6 minutes after arc initiation is recorded as one smelting operation), and the ingot is turned over after each smelting to mix different elements and components and improve the uniformity of the alloy ingot. Multiple smelting helps to refine the grain structure of the alloy ingot and improve the mechanical properties of the material; it also helps to homogenize the alloy components and reduce local component segregation, thereby ensuring the stability of the overall performance, and is also beneficial to subsequent solid solution and other links.

[0051] In step 1, after the arc is struck, the current during smelting is adjusted according to the molten state of the metal and the molten flow state. Usually, a current of 120~180 A is suitable, for example, 139A is selected.

[0052] In step 1, after the smelting is completed, the temperature is naturally lowered to room temperature in an inert atmosphere such as an argon atmosphere to obtain a smelted alloy ingot.

[0053] In step 2, the post-treatment includes solution treatment and quenching.

[0054] Among them, according to the melting point of each alloy of the raw material and the purpose of suppressing the long-range martensitic phase transformation, the temperature of the solid solution is determined to be 1000 ~ 1100 ° C, for example, 1000 ° C. When the temperature is higher than 1100 ° C, for example, at 1200 ° C, the raw material will melt, resulting in a large amount of loss and oxidation. At the same time, too high a temperature may lead to coarse grains and reduce corrosion resistance and mechanical properties; the melting point of Cu with the lowest melting point in the raw material is about 1083.4 ° C. If the temperature is lower than 1000 ° C, the internal atomic diffusion process, that is, the solid solution process, cannot be carried out well. At this time, the elements cannot be fully dissolved, and the effect of eliminating internal stress, improving organizational structure and improving performance cannot be achieved. Only in the temperature range of 1000 ~ 1100 ° C can the purpose of solid solution treatment be achieved to the greatest extent.

[0055] In step 2, the solid solution time is 3 to 6 hours, for example, 3 hours. When the time is less than 3 hours, the diffusion of the alloy elements of the raw materials is not complete, and the mechanical properties of the high entropy alloy do not have obvious advantages. When the time is longer than 6 hours, due to the high solubility of the raw materials, the strength of the high entropy alloy is improved, but the superelasticity is greatly reduced.

[0056] In step 2, the heating rate during solid solution is 8~12℃ / min, for example, 10℃ / min. In order to obtain high-quality solid solution effect, the heating rate should be controlled within a reasonable range. On the one hand, too slow heating rate is likely to lead to excessively large grain size, increase the risk of precipitation of dispersed precipitate phase at grain boundaries, reduce the strength and toughness of the alloy, and at the same time, it is not conducive to the rapid dissolution of the solid solution and reduces the solid solution effect; on the other hand, too fast heating and cooling rates are likely to cause large thermal stress inside the metal and local melting of low-melting-point structures to cause heat burning, which seriously deteriorates the metal properties. At the same time, too fast heating rate is likely to damage the heating equipment.

[0057] In step 2, before solid solution, first evacuate the chamber and purge it with an inert gas such as argon 3 to 5 times, then evacuate the chamber to a negative pressure state (less than 1×10 -3 Pa) and use inert gas such as argon as protective gas to maintain a negative pressure state of 0.03~0.06Pa (relative pressure).

[0058] In step 2, the quenching is preferably water quenching. First, water quenching has an extremely fast cooling rate, which not only helps to make the internal structure of the metal more dense, thereby improving the hardness and strength of the high entropy alloy, but also has better hardenability, and can also ensure that the dissolved alloy elements diffuse as little as possible during the cooling process; in addition, water quenching is low in cost and easy to use and subsequent processing.

[0059] On the other hand, the high entropy alloy described in the first aspect or the high entropy alloy prepared according to the method described in the second aspect provided by the present invention is used in deep sea detection sensing or deep space detection sensing.

[0060] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.

[0061] Example 1

[0062] Select metal raw materials with a purity of 99.95% or more in the following mass ratio: Ti 9.7%, Zr 18.4%, Hf36.0%, Ni 17.8%, Co 14.3%, Cu 3.8%, with a metal mass of 40g, for standby use;

[0063] The Ti balls and the above raw materials were placed in the furnace chamber of the arc melting furnace, and then vacuumed and further washed with argon gas for 3 times, and then vacuumed to a pressure value less than 2×10 -3 Pa, at this time, argon gas is filled as a protective gas to make the furnace chamber pressure at 0.05Pa; Ti ball is used to strike the arc and melt the Ti ball for 60s, and the raw material is melted at 139A for 3min. This process is repeated 6 times, and the surface is turned over after each melting process. After that, the furnace chamber is cooled to room temperature to obtain the melted alloy ingot;

[0064] The alloy ingot was sealed and vacuumed, and then purged with argon gas for 3 times, and then vacuumed to a pressure of 1×10 -3 Pa; then argon was used as the protective gas, maintained at 0.05 Pa, and the temperature was raised from room temperature 25°C to 1000°C at a heating rate of 10°C / min, and kept at this temperature for 3 hours. After the insulation was completed, water quenching was performed to obtain a high entropy alloy, which was recorded as 1# alloy.

[0065] The obtained high entropy alloy wire was cut into cylinders with a diameter of 4 mm and a height of 8 mm. The variable temperature compression of the cylinders at -50°C, -25°C, 0°C, 25°C, 50°C, 25°C, 100°C, and 125°C was measured by a mechanical testing machine. The static modulus temperature curves were as follows: Figure 1 As shown in the figure, it can be seen that the prepared high entropy alloy exhibits a constant elastic effect under static stress loading in the temperature range of -50℃ to 125℃, that is, in the temperature range of 175℃, and its elastic modulus temperature coefficient is 8.83×10 -5 / ℃.

[0066] The obtained high entropy alloy wire was cut into a 25×10×3 mm cuboid and subjected to a dynamic modulus test on a dynamic thermomechanical analyzer. The obtained dynamic modulus temperature curve is shown in Figure 2 As shown in the alloy curve of No. 1, it can be seen that the prepared high entropy alloy exhibits a constant elastic effect in the temperature range of -50°C to 125°C, that is, 175°C, under stress loading at multiple frequencies.

[0067] The cylindrical high entropy alloy cut above was subjected to compression cycle test at room temperature by a mechanical testing machine, and the obtained room temperature compression cycle stress-strain curve is as follows: Figure 3 As shown, it can be seen that the prepared high entropy alloy has superelasticity, which exhibits a recoverable strain of about 3.6%.

[0068] The cylindrical high entropy alloy cut above was subjected to room temperature compression fracture test by a mechanical testing machine, and the room temperature compression fracture curve obtained was as follows: Figure 4As shown in the 1# alloy curve, it can be seen that it has a compressive strength of about 2GPa and a compressive fracture strain of about 14.3%. In addition, its yield strength is about 729MPa and its elastic modulus is about 60.08GPa, showing good mechanical properties.

[0069] Example 2

[0070] Select metal raw materials with a purity of 99.95% or more and the following mass ratio: Ti 9.6%, Zr 18.4%, Hf 35.9%, Ni 17.7%, Co 10.7%, Cu 7.7%, the metal mass is 40g, and set aside;

[0071] The Ti balls and the above raw materials were placed in the furnace chamber of the arc melting furnace, and then vacuumed and further washed with argon gas for 3 times, and then vacuumed to a pressure value less than 2×10 -3 Pa, at this time, argon gas is filled as a protective gas to make the furnace chamber pressure at 0.05Pa; Ti ball is used to strike the arc and melt the Ti ball for 60s, and the raw material is melted at 139A for 3min. This process is repeated 6 times, and the raw material is turned over after each melting. After that, the furnace chamber is cooled to room temperature to obtain the melted alloy ingot;

[0072] The alloy ingot was sealed and vacuumed, and then purged with argon gas for 3 times, and then vacuumed to a pressure of 1×10 -3 Pa; then argon was used as the protective gas, maintained at 0.05 Pa, and the temperature was raised from room temperature 25°C to 1000°C at a heating rate of 10°C / min, and kept at this temperature for 3 hours. After the insulation was completed, water quenching was performed to obtain a high entropy alloy, which was recorded as 2# alloy.

[0073] The obtained high entropy alloy wire was cut into a 25×10×3 mm cuboid and subjected to a dynamic modulus test on a dynamic thermomechanical analyzer. The obtained dynamic modulus temperature curve is shown in Figure 2 As shown in the 2# alloy curve, it can be seen that the prepared high entropy alloy exhibits a constant elastic effect in the temperature range of 50°C to 200°C, i.e. 150°C, under stress loading at multiple frequencies.

[0074] The obtained high entropy alloy wire was cut into a cylinder with a diameter of 4 mm and a height of 8 mm, and a compression cycle test was performed at room temperature using a mechanical testing machine. The obtained room temperature compression cycle stress-strain curve is shown in Figure 5 As shown, it can be seen that the prepared high entropy alloy has superelasticity, which exhibits a recoverable strain of about 3%.

[0075] The cylindrical high entropy alloy cut above was subjected to room temperature compression fracture test, and the room temperature compression fracture curve obtained was as follows: Figure 4As shown in the 2# alloy curve, it can be seen that it has a compressive strength of about 1.9 GPa and a compressive fracture strain of about 19.8%. In addition, its yield strength is about 736 MPa and its elastic modulus is about 46.9 GPa, showing good mechanical properties.

[0076] Example 3

[0077] Select metal raw materials with a purity of 99.95% or more and the following mass ratio: Ti 9.7%, Zr 18.4%, Hf 36.1%, Ni 17.8%, Co 16.1%, Cu 1.9%, the metal mass is 40g, and set aside;

[0078] The Ti balls and the above raw materials were placed in the furnace chamber of the arc melting furnace, and then vacuumed and further washed with argon gas for 3 times, and then vacuumed to a pressure value less than 2×10 -3 Pa, at this time, argon gas is filled as a protective gas to make the furnace chamber pressure at 0.05Pa; Ti ball is used to strike the arc and melt the Ti ball for 60s, and the raw material is melted at 139A for 3min. This process is repeated 6 times, and the raw material is turned over after each melting. After that, the furnace chamber is cooled to room temperature to obtain the melted alloy ingot;

[0079] The alloy ingot was sealed and vacuumed, and then purged with argon gas for 3 times, and then vacuumed to a pressure of 1×10 -3 Pa; then argon was used as the protective gas, maintained at 0.05 Pa, and the temperature was raised from room temperature 25°C to 1000°C at a heating rate of 10°C / min, and kept at this temperature for 3 hours. After the insulation was completed, water quenching was performed to obtain a high entropy alloy, which was recorded as 3# alloy.

[0080] The obtained high entropy alloy wire was cut into a 25×10×3 mm cuboid and subjected to a dynamic modulus test on a dynamic thermomechanical analyzer. The obtained dynamic modulus temperature curve is shown in Figure 2 As shown in the 3# alloy curve, it can be seen that the prepared high entropy alloy exhibits a constant elastic effect in the temperature range of -100°C to 30°C, i.e. 130°C, under stress loading at multiple frequencies.

[0081] The obtained high entropy alloy wire was cut into a cylinder with a diameter of 4 mm and a height of 8 mm, and a compression cycle test was performed at room temperature using a mechanical testing machine. The obtained room temperature compression cycle stress-strain curve is shown in Figure 6 As shown, it can be seen that the prepared high entropy alloy has superelasticity, which exhibits a recoverable strain of about 2.5%.

[0082] The cylindrical high entropy alloy cut above was subjected to room temperature compression fracture test, and the room temperature compression fracture curve obtained was as follows: Figure 4As shown in the 3# alloy curve, it can be seen that it has a compressive strength of about 1.8 GPa and a compressive fracture strain of about 17.4%. In addition, its yield strength is about 1540 MPa and its elastic modulus is about 90.56 GPa, showing excellent mechanical properties.

[0083] It can be seen from Examples 1-3 that the high entropy alloy of the present invention has both constant elasticity and superelasticity and has good mechanical properties. The high entropy alloy in Example 1 has constant elasticity within a temperature range of 175°C (-50~125°C), that is, it has the widest constant elasticity temperature range, and has the largest recoverable strain, that is, it has the best constant elasticity and superelasticity, and has the highest compressive strength, and has the best comprehensive performance.

[0084] Comparative Example 1

[0085] A high entropy alloy was prepared in a similar manner to Example 1, except that no Cu was added, namely:

[0086] Select metal raw materials with a purity of 99.95% or more and the following mass ratio: Ti 9.7%, Zr 18.5%, Hf 36.1%, Ni 17.8%, Co 17.9%, the metal mass is 40g, and set aside;

[0087] The Ti balls and the above raw materials were placed in the furnace chamber of the arc melting furnace, and then vacuumed and further washed with argon gas for 3 times, and then vacuumed to a pressure value less than 2×10 -3 Pa, at this time, argon gas is filled as a protective gas to make the furnace chamber pressure at 0.05Pa; Ti ball is used to strike the arc and melt the Ti ball for 60s, and the raw material is melted at 139A for 3min. This process is repeated 6 times, and the raw material is turned over after each melting. After that, the furnace chamber is cooled to room temperature to obtain the melted alloy ingot;

[0088] The alloy ingot was sealed and vacuumed, and then purged with argon gas for 3 times, and then vacuumed to a pressure of 1×10 -3 Pa; then argon is used as the protective gas, maintained at 0.05Pa, and the temperature is raised from room temperature 25°C to 1000°C at a heating rate of 10°C / min, and this temperature is kept for 3h. After the heat preservation is completed, water quenching is performed to obtain a high entropy alloy.

[0089] The obtained high entropy alloy wire was cut into cylinders with a diameter of 4 mm and a height of 8 mm, and a compression cycle test was carried out at room temperature using a mechanical testing machine. The results showed that the obtained high entropy alloy did not have superelasticity, but only the linear elasticity of the material itself.

[0090] The obtained high entropy alloy wire was cut into 25×10×3mm rectangles and subjected to dynamic modulus test on a dynamic thermomechanical analyzer. The results showed that the obtained high entropy alloy had constant elasticity in a wide temperature range of 500°C; a room temperature compression fracture test was carried out, and the results showed that it had a compressive strength of 2GPa. In summary, the alloy has excellent mechanical properties and constant elasticity in a wide temperature range, but it does not have superelasticity.

[0091] Comparative Example 2

[0092] A high entropy alloy was prepared in a similar manner to Example 1, except that the raw material composition exceeded the aforementioned range and the solution time was 2 hours, namely:

[0093] Select metal raw materials with a purity of 99.95% or more and the following mass ratio: Ti 9.6%, Zr 18.3%, Hf 35.8%, Ni 17.7%, Co 7.1%, Cu 11.5%, the metal mass is 40g, and set aside;

[0094] The Ti balls and the above raw materials were placed in the furnace chamber of the arc melting furnace, and then vacuumed and further washed with argon gas for 3 times, and then vacuumed to a pressure value less than 2×10 -3 Pa, at this time, argon gas is filled as a protective gas to make the furnace chamber pressure at 0.05Pa; Ti ball is used to strike the arc and melt the Ti ball for 60s, and the raw material is melted at 139A for 3min. This process is repeated 6 times, and the raw material is turned over after each melting. After that, the furnace chamber is cooled to room temperature to obtain the melted alloy ingot;

[0095] The alloy ingot was sealed and vacuumed, and then purged with argon for 3 times. Then, argon was used as the protective gas, maintained at 0.05 Pa, and vacuumed to a pressure of 1×10 -3 Pa; then the temperature is raised from room temperature (25°C) to 1000°C at a heating rate of 10°C / min, and kept at this temperature for 2h. After the heat preservation is completed, water quenching is performed to obtain a high entropy alloy.

[0096] The obtained high entropy alloy wire was cut into a cylinder with a diameter of 4mm and a height of 8mm, and a compression cycle test was carried out at room temperature using a mechanical testing machine. It had a superelastic strain of about 3.5% at room temperature; the elastic modulus of the obtained high entropy alloy at 100℃, 25℃ and -75℃ were 70GPa, 42GPa and 30GPa respectively, which was much larger than the requirement of constant elasticity. The obtained high entropy alloy exhibited superelasticity in a wide temperature range, but the modulus changed dramatically with temperature and did not have a constant elastic effect.

[0097] Comparative Example 3

[0098] A high entropy alloy was prepared in a similar manner to Example 1, except that there was no solution treatment and water quenching, namely:

[0099] Select metal raw materials with a purity of 99.95% or more in the following mass ratio: Ti 9.7%, Zr 18.4%, Hf36.0%, Ni 17.8%, Co 14.3%, Cu 3.8%, with a metal mass of 40g, for standby use;

[0100] The Ti balls and the above raw materials were placed in the furnace chamber of the arc melting furnace, and then vacuumed and further washed with argon gas for 3 times, and then vacuumed to a pressure value less than 2×10 -3 Pa, at this time, argon gas is filled as a protective gas to make the furnace chamber pressure at 0.05Pa; Ti ball is used to strike the arc and melt the Ti ball for 60s, and the raw material is melted at 139A for 3min. This process is repeated 6 times, and the raw material is turned over after each melting. After that, the furnace chamber is cooled to room temperature to obtain the melted alloy ingot;

[0101] The surface of the alloy ingot is polished, and this product is recorded as a high entropy alloy. The obtained high entropy alloy wire is cut into a cylinder with a diameter of 4mm and a height of 8mm, and a compression cycle test is performed at room temperature using a mechanical testing machine. The results show that the obtained high entropy alloy has a superelasticity of about 3%.

[0102] The obtained high entropy alloy wire was cut into 25×10×3mm cuboids and subjected to dynamic modulus test on a dynamic thermomechanical analyzer. The results showed that the obtained high entropy alloy had a relatively small stage of modulus change, that is, it did not have constant elasticity.

[0103] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A high entropy alloy, characterized in that: The total mass of the high entropy alloy is 100 wt.%, which includes the following components (wt.%): Ti is 5-10%, Zr is 15-20%, Hf is 35-40%, Ni is 15-20%, Co is 10-20%, and the remaining component is Cu.

2. The high entropy alloy according to claim 1, characterized in that Preferably, the temperature coefficient of elastic modulus of the high entropy alloy in the temperature range of 130-175°C is 1×10 -5 ~1×10 -4 / ℃.

3. The high entropy alloy according to claim 1, characterized in that The recoverable strain of the high entropy alloy is 2.5-3.6%.

4. The high entropy alloy according to claim 1, characterized in that The compressive strength of the high entropy alloy is 1.8~2GPa.

5. The high entropy alloy according to claim 1, characterized in that: The compressive fracture strain of the high entropy alloy is 14.3-19.8%.

6. The high entropy alloy according to claim 1, characterized in that The elastic modulus of the high entropy alloy is 46.9~90.56Gpa.

7. A method for preparing the high entropy alloy according to any one of claims 1 to 6, characterized in that: The method comprises: Step 1, smelting Ti, Zr, Hf, Ni, Co and Cu to obtain an alloy ingot; Step 2: post-processing the alloy ingot to obtain the high entropy alloy.

8. The method according to claim 6, characterized in that In step 1, the purity of Ti, Zr, Hf, Ni, Co and Cu is not less than 99.95%.

9. The method according to claim 6, characterized in that In step 2, the post-treatment includes solution treatment and quenching.

10. Application of the high entropy alloy according to any one of claims 1 to 6 or the high entropy alloy prepared according to the method according to any one of claims 7 to 9 in deep sea detection sensing.

Citation Information

Cited By

  • Preparation method of high-entropy alloy with constant-elasticity and super-elasticity characteristics, alloy and application

    CN120666203A

  • Preparation method of high-entropy alloy with constant and super-elastic properties, alloy and application

    CN120666203B